Censorship in People’s Poland - Łęcicki, Grzegorz (Žurnalistikos tyrimai, 2017)
The range and power of how media is transferred – since the time when printing machines were invented in the fifteenth century – has been quite a challenge for specific environments, institutions, ideas and beliefs; for both, the clerical and secular authorities wanted to influence the distribution of content. The actions of the Catholic Church, in this respect, were to exclude the promotion of heretical ideas, whereas the political power cared about shaping the attitudes of obedience and loyalty (Pokorna-Ignatowicz, 2002). Attempts made to restrict the freedom of the printed word had failed because not all of the authors, publishers and printers conformed to the Church and its rulers; instead, they spread opinions in accordance with their convictions. Reformation can be considered as the first ideological revolution, the success of which was closely related with media coverage (in this case – with the use of print) (Łęcicki, 2013).